Numerical Simulations and the Design of Magnetic Field-Enhanced Electron Impact Ion Source with Hollow Cylinder Structure. (25th January 2020) - Qi, Guochen; Tian, Di; Gao, Guolun; Liu, Guangda; Qiu, Chunling; Long, Tao
Abstract : An electron impact ion source-adopted magnetic field-enhanced technology has been designed for enhancing the electron intensity and the ionization efficiency. Based on the ion optic focus mechanism, an electron impact ionization source was designed, and the electron entrance into the ionization chamber was designed with a hollow cylinder structure to improve the ion extraction efficiency. Numerical simulation and optimal geometry were optimized by SIMION 8.0 to provide higher electron intensity and ion transmission efficiency. To improve the electron intensity, the influence of the filament potential and magnetic intensity was investigated, and the values of 70 eV and 150 Gs were chosen in our apparatus. Based on the optimal parameters, the air in the lab and oxygen gas was detected by the homemade apparatus, and the ion intensity was detected in the positive and negative ion modes, respectively. The homemade electron impact ion source apparatus has the potential to enhance ionization efficiency applied in the mass spectrometer ionization source.